In the Pursuit of Research: Investigating the Difficulties Faced by Aspiring Young Researchers in Bangladesh - Jubair, Hassan; Mehenaz, Mithela; Islam, MD. Merajul (COMPETITIVE: Journal of Education, 2025)
Research is a fundamental driver of academic growth, scientific innovation, and national development. However, aspiring young researchers in Bangladesh face significant barriers that hinder their engagement in scholarly activities. This study investigates the challenges encountered by high school and undergraduate students in Bangladesh in pursuing research, focusing on systemic, financial, and institutional obstacles. Using a mixed-methods approach, data were collected from students through surveys and analyzed to identify key factors impeding research participation. The findings reveal that the primary challenges include a lack of mentorship, limited access to research resources, financial constraints, and insufficient institutional support. Furthermore, the study highlights a critical gap in students' awareness of research methodologies, academic publishing processes, and funding opportunities. A significant proportion of respondents expressed difficulty in obtaining guidance from teachers or academic institutions, with many unaware of how to publish their work in reputable journals. These barriers collectively discourage students from engaging in research, ultimately limiting the country’s academic progress. This study contributes to the existing literature by providing empirical insights into the difficulties faced by young researchers in Bangladesh. The findings underscore the need for targeted policy interventions, including the integration of research training into curricula, financial support programs, mentorship initiatives, and improved access to academic resources. By addressing these challenges, educational institutions and policymakers can foster a research-friendly environment that nurtures the next generation of scholars.